Mars methane analogue mission: Mission simulation and rover operations at Jeffrey Mine and Norbestos Mine Quebec, Canada. Issue 10 (15th May 2015) - Qadi, A.; Cloutis, E.; Samson, C.; Whyte, L.; Ellery, A.; Bell, J.F.; Berard, G.; Boivin, A.; Haddad, E.; Lavoie, J.; Jamroz, W.; Kruzelecky, R.; et al.
Abstract The Canadian Space Agency (CSA), through its Analogue Missions program, supported a microrover-based analogue mission designed to simulate a Mars rover mission geared toward identifying and characterizing methane emissions on Mars. The analogue mission included two, progressively more complex, deployments in open-pit asbestos mines where methane can be generated from the weathering of olivine into serpentine: the Jeffrey mine deployment (June 2011) and the Norbestos mine deployment (June 2012). At the Jeffrey Mine, testing was conducted over 4 days using a modified off-the-shelf Pioneer rover and scientific instruments including Raman spectrometer, Picarro methane detector, hyperspectral point spectrometer and electromagnetic induction sounder for testing rock and gas samples. At the Norbestos Mine, we used the research Kapvik microrover which features enhanced autonomous navigation capabilities and a wider array of scientific instruments. This paper describes the rover operations in terms of planning, deployment, communication and equipment setup, rover path parameters and instrument performance. Overall, the deployments suggest that a search strategy of "follow the methane" is not practical given the mechanisms of methane dispersion. Rather, identification of features related to methane sources based on image tone/color and texture from panoramic imagery is more profitable.